E-Satisfaction as a Mediating Variable Influence of E-Service Quality on E-WOM in Linkaja Syariah Users - Zuhratun Nisak Risnia; Nihayatu Aslamatis Solekah (MALIA: Jurnal Ekonomi Islam, 2023)
The purpose of this study is to investigate the influence of e-service quality on E-WOM through the mediating variable of e-satisfaction among Linkaja Syariah users in Malang City. Because the use of Linkaja Syariah in Malang City is very popular, researchers are interested in conducting a study on electronic services and Linkaja Syariah user satisfaction that can affect digital marketing. This study uses a quantitative method and data processing is done using Smartpls 0.4 with 170 respondents. The results of the study indicate that e-service quality has a significant positive influence on E-WOM, and also has a significant positive influence on e-satisfaction. E-satisfaction also has a significant positive influence on E-WOM, so it can be said that e-satisfaction is a mediating variable between e-service quality and E-WOM.